2002
DOI: 10.1524/zkri.217.10.497.20795
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of short and long range atomic order in nanocrystalline diamonds with application of powder diffractometry

Abstract: Fundamental limitations, with respect to nanocrystalline materials, of the traditional elaboration of powder diffraction data like the Rietveld method are discussed. A tentative method of the analysis of powder diffraction patterns of nanocrystals based on the examination of the variation of lattice parameters calculated from individual Bragg lines (named the “

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 35 publications
4
39
0
Order By: Relevance
“…[6,7,33,34] On the other hand, as small nanoparticles show a nonuniform structure, additional extensions to the modelling of nanoparticle structure may be needed to accommodate core/shell structure model. [35,36] This was noted recently on in a study by Palosz et al [36] where they reported the limitations and the perspectives of diffraction studies of the atomic structure of nanoparticles.…”
Section: Introductionmentioning
confidence: 87%
“…[6,7,33,34] On the other hand, as small nanoparticles show a nonuniform structure, additional extensions to the modelling of nanoparticle structure may be needed to accommodate core/shell structure model. [35,36] This was noted recently on in a study by Palosz et al [36] where they reported the limitations and the perspectives of diffraction studies of the atomic structure of nanoparticles.…”
Section: Introductionmentioning
confidence: 87%
“…Both plots can be used for examination of the core-shell structure of a nanocrystal. While alp-Q dependencies were already used for evaluation of core-shell models of nanocrystals [9][10][11][12][13], we are not aware of any earlier attempt to use PDF analysis for examination of the core-shell structure of nanocrystals; although plots of relative changes Dr i =r i have been measured experimentally for diamond and SiC [18], they were not used for evaluation of core-shell models.…”
Section: Distribution Of Individual Inter-atomic Distances At Pdf Plotmentioning
confidence: 99%
“…The solution might be in the analysis of the experimental alp-Q relation through seeking a model which gives theoretical alp-Q dependence similar to the experimental one. We used this approach for evaluation of the core-shell structure of nanocrystalline diamond and SiC [10][11][12][13]; the methodology of doing such an alp-Q analysis has been published previously [9] and is not discussed here.…”
mentioning
confidence: 99%
“…However, it was observed for 5 nm grain size diamond powders that the broadening of peak profiles is resulted rather by the small crystallite size and the stacking faults and not by dislocations, see Fig. 17 [112]. Assuming a shell-core model of the diamond nanoparticles, the defect structure of the internal region and the shell strains were obtained from the line broadening and the diffraction vector dependence of the apparent lattice parameter, respectively [112][113][114].…”
Section: Carbon and Diamondmentioning
confidence: 99%